The mighty Currawongs : & other stories - Doyle, Brian, 1956 November 6-2017 May 27 (Red Hen Press, 2016)
"A collection of headlong tales by Oregon author Brian Doyle - exploring such riveting and peculiar topics as chess in the Levant, tailors who specialize in holes, how to report stigmata to your attending physician, the intense hilarity of basketball, how to have a bitter verbal marital fight in your car, an all-Chinese football team in Australia, soccer and Catholicism, what it's like to be in a ska band, a singing Korean baker, an archbishop who loses his faith between the salad and the entrée genius Girl Scouts who save a radio station, and a baby born from a lake in Illinois. And some other fascinating stories. Really. Trust us"--